2017
DOI: 10.1371/journal.pone.0178052
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing interest in recreational sports participation and its rural-urban disparity

Abstract: ObjectivesRecreational sports are important leisure activities. However, most studies investigating barrier factors and motivation for participation in recreational sports have been limited to specific areas (e.g., a city or school) or demographic groups (e.g., adolescents). Therefore, this study set out to gain a more comprehensive understanding of the behavioral and socioeconomic factors influencing interest in recreational sports participation in Taiwan, as well as to evaluate the effect of any urban-rural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 30 publications
4
23
0
Order By: Relevance
“…Adolescents in Mexico City living in a place with high urbanicity would spend 8% more time in sport activities than their peers living in a place with low urbanicity, while adolescents living in a place with high urbanicity in Oaxaca would spend 4.5% less time in sports than their peers living in a place with low urbanicity. Previous evidence coincides with the positive association found in Mexico City; for example, in Taiwan adolescents living in rural areas were less interested in recreational sports than adolescents living in urban areas [ 44 ]. Further, parents of children from urban schools were more likely to drive their children to sport facilities than parents from rural areas, and the weekly frequency of sports club attendance was higher amongst urban children [ 45 ].…”
Section: Discussionsupporting
confidence: 71%
“…Adolescents in Mexico City living in a place with high urbanicity would spend 8% more time in sport activities than their peers living in a place with low urbanicity, while adolescents living in a place with high urbanicity in Oaxaca would spend 4.5% less time in sports than their peers living in a place with low urbanicity. Previous evidence coincides with the positive association found in Mexico City; for example, in Taiwan adolescents living in rural areas were less interested in recreational sports than adolescents living in urban areas [ 44 ]. Further, parents of children from urban schools were more likely to drive their children to sport facilities than parents from rural areas, and the weekly frequency of sports club attendance was higher amongst urban children [ 45 ].…”
Section: Discussionsupporting
confidence: 71%
“…Although there are no studies documenting coaches’ perceptions on factors motivating schoolboys to participate in rugby, our results are consistent with studies investigating general sports participation among children, adolescents and adults [12, 14, 15, 17, 18]. A study conducted using college students’ found that enjoyment and the need for challenges were predominant motivational factors for sport participation [12].…”
Section: Discussionsupporting
confidence: 88%
“…However, a higher percentage of urban adolescents with OW practice 60 minutes of PA per day. This could be related to greater access to sports activities [45,48] and a greater support/monitoring of parents in the healthy behavior of their children in urban areas than in rural areas [49]. The smaller number of adolescents classified as OW and O, or the differences of sex and age could distort the results found.…”
Section: Discussionmentioning
confidence: 95%